1994
DOI: 10.1159/000310447
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor in the Topical Treatment of Herpetic Corneal Ulcers

Abstract: The tolerability and efficacy of epidermal growth factor (EGF) in the topical treatment of herpetic corneal ulcers in addition to topical acyclovir have been evaluated in a double-blind, placebo-controlled, randomized study in two groups of patients. The time required for complete reepithelialization of the cornea was recorded, and the data obtained were analyzed statistically. In the EGF group, the reepithelialization was significantly faster than in the control group. Tolerability of EGF was always excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…[37][38][39] Similarly, toxicity studies in rabbits did not reveal differences between control and EGFtreated rabbits. 28 However, other studies in rabbits have revealed neovascularization and inflammation associated with EGF treatment, using a dose of 50 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] Similarly, toxicity studies in rabbits did not reveal differences between control and EGFtreated rabbits. 28 However, other studies in rabbits have revealed neovascularization and inflammation associated with EGF treatment, using a dose of 50 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore, EGF has proven to be beneficial during clinical studies in humans. [36][37][38][39] Corneal epithelium plays a crucial role as a protective barrier for the eye. Keratitis can have serious consequences in horses, because they are prone to develop secondary mycotic infections.…”
mentioning
confidence: 99%
“… 1 Thirteen of 46 randomised, double-masked trials are not tabulated because two-week outcome data were not provided (Burns 1963; Wang 2004) or because comparative interventions not listed in this table were studied (Cellini 1994; Colin 1984; Coster 1977a; Guerra 1979; Parlato 1985; Sundmacher 1976b; Sundmacher 1978a; Sundmacher 1984a; Sundmacher 1985; Uchida 1981; Uchida 1982). …”
Section: Figurementioning
confidence: 99%
“… 1 Thirteen of 46 randomised, double-masked trials are not tabulated because two-week outcome data were not provided (Burns 1963; Wang 2004) or because comparative interventions not listed in this table were studied (Cellini 1994; Colin 1984; Coster 1977a; Guerra 1979; Parlato 1985; Sundmacher 1976b; Sundmacher 1978a; Sundmacher 1984a; Sundmacher 1985; Uchida 1981; Uchida 1982) NA: not applicable (single study available for evaluation) …”
Section: Figurementioning
confidence: 99%